Association of interpregnancy interval with small/large for gestational age birth for women with two consecutive singleton deliveries: a hospital-based analysis - Gao-jie FAN; Qing LIU; Kai CHEN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore the effect of interpregnancy interval on small for gestational age (SGA) and large for gestational age (LGA) birth and to provide evidence to the consultation about multiparous pregnancy and the development of public health policies. MethodsComplete information on 7 752 mother-infant pairs of two consecutive delivery from 2015 through 2020 were collected from Guangdong Provincial Maternal and Child Health Hospital. The mothers' interpregnancy intervals were were divided into 5 groups of < 6, 6 - 11, 12 - 17, 18 - 23, ≥ 24 months. Logistic regression model was adopted in the analysis on the association of interpregnancy interval with small/large for gestational age birth. ResultsFor all the mothers aged 26.57 ± 4.03 years at their second childbirth, the incidence of SGA birth was 12.40% and that of LGA birth was 4.72%, respectively. Logistic regression results showed that short interpregnancy interval was significantly associated with SGA birth after adjusting potential confounders. Compared to the mothers with the interpregnancy interval of 12 - 17 months, the mothers with shorter interpregnancy intervals had a significantly increased risk of SGA birth, with the odds ratios of 1.42 (95% confidence interval: 1.14 - 1.79) for the mothers with the interpregnancy interval of < 6 months and 1.36 (1.13 - 1.64) for the mothers with the interpregnancy interval of 6 - 11 months. No significant association between interpregnancy interval and LGA birth was observed. ConclusionInterpregnancy interval less than 12 months is an independent risk factor for small for gestational age birth. The optimal interpregnancy interval should be emphasized in prenatal consultation and health education to reduce the risk of adverse birth outcome.